1985
DOI: 10.1111/j.1469-8137.1985.tb02846.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical Leaf Concentrations for Deficiencies of Nitrogen, Potassium, Phosphorus, Sulphur, and Magnesium in Perennial Ryegrass

Abstract: SUMMARYCritical leaf concentrations for deficiency of nitrogen, potassium, phosphorus, sulphur, and magnesium were estimated for perennial ryegrass {Lolium perenne L.) grown in sand culture. The values associated with a 10% reduction in dry matter yield were as follows (all results expressed as g kg~^ DM except for the nitrate-nitrogen value which appears as /ig g~^ DM): Kjeldahl-nitrogen 32; nitrate-nitrogen 500; potassium 28; phosphorus 21; sulphur 18; and magnesium 0-7. A major difference between the critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
3

Year Published

1987
1987
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 26 publications
3
61
0
3
Order By: Relevance
“…Nitrogen in harvested plant material recorded with OMF and urea applied at 300 kg ha −1 of N were relatively lower (range: 2.2-2.8%) than a critical leaf concentration for deficiency of N of 3.2% by weight (Smith, Cornforth, and Henderson 1985). This threshold value is defined as N concentration in the leaves below which reductions in maximum yield of 10% or greater may occur due to insufficient supply of that nutrient (Smith, Cornforth, and Henderson 1985). However, nitrogen in harvested plant material with OMF and urea were within the range required by high-producing dairy cattle (Aavola and Kärner 2008).…”
Section: Fertilizer Application Effects On Cropmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen in harvested plant material recorded with OMF and urea applied at 300 kg ha −1 of N were relatively lower (range: 2.2-2.8%) than a critical leaf concentration for deficiency of N of 3.2% by weight (Smith, Cornforth, and Henderson 1985). This threshold value is defined as N concentration in the leaves below which reductions in maximum yield of 10% or greater may occur due to insufficient supply of that nutrient (Smith, Cornforth, and Henderson 1985). However, nitrogen in harvested plant material with OMF and urea were within the range required by high-producing dairy cattle (Aavola and Kärner 2008).…”
Section: Fertilizer Application Effects On Cropmentioning
confidence: 99%
“…Low N supply to grass crops compromises growth rate, tiller density, and biomass production, and reduces N concentration in plant (Wilman and Mohamed 1980;Delagarde, Peyraud, and Delaby 1997). Nitrogen in harvested plant material recorded with OMF and urea applied at 300 kg ha −1 of N were relatively lower (range: 2.2-2.8%) than a critical leaf concentration for deficiency of N of 3.2% by weight (Smith, Cornforth, and Henderson 1985). This threshold value is defined as N concentration in the leaves below which reductions in maximum yield of 10% or greater may occur due to insufficient supply of that nutrient (Smith, Cornforth, and Henderson 1985).…”
Section: Fertilizer Application Effects On Cropmentioning
confidence: 99%
“…Yin and Vyn (2004) estimated the critical leaf K concentration for maximum yield of soybeans to be 25.9 g kg -1 . Smith et al (1985) showed that perennial ryegrass produced 98% of the maximum dry matter where K concentrations in the shoots were greater than 36 g kg -1 .…”
Section: Critical K Concentration Of Stevia Leafmentioning
confidence: 99%
“…However, increases in solution K concentration reduce uptake of both Ca and Mg by plants, even at higher solution K levels resulting in less than maximum forage yield. Smith et al (1985) reported that Mg concentrations level out at 1.9 g kg" when herbage contains 25 g K kg"; whereas Ca concentration continues to decrease to a low of 6 g kg" as forage K increases to 65 g K kg". High herbage K levels also depresses Mg and Ca absorption by ruminants.…”
Section: Magnesium X Potassium X Calciummentioning
confidence: 99%